Perfil de suscetibilidade e atividade antimicrobiana sobre biofilmes de micobactérias não tuberculosas de crescimento rápido - Flores, Vanessa da Costa (2014)
Rapidly growing mycobacteria (RGM) are opportunistic human pathogens that are present in our environment. When in biofilms form, mycobacteria are highly resistant to antibacterial treatments. The comprehension of factors that cause mycobacteriosis treatments to fail, e.g., biofilm formation, contributes to the elucidation of the pathogenic potential and the drug resistance shown by these microorganisms. The tested antimicrobials were amikacin, ciprofloxacin, clarithromycin, doxycycline, imipenem and sulfamethoxazole, which are ordinarily employed in the treatment of mycobacteriosis. For each drug, it was evaluated the susceptibility of the pathogen, the ability to inhibit biofilm formation and the resistance of biofilms to antimicrobial activity. Results showed that although the tested antimicrobials are used as an alternative therapy for RGM, Mycobacterium abscessus presented to be resistant to clarithromycin and Mycobacterium massiliense showed a resistant profile to clarithromycin and sulfamethoxazole. Furthermore, the inhibition of biofilm formation and its destruction have not been fully met. The susceptibility profiles found emphasize the need for the determination of drug sensitivity. Considering that the biofilms are a known form of bacterial resistance, the failure of alternatives to inhibit or destroy biofilms can trigger the recurrence of infections.